Labour law and debt of life: Acceptance speech of the Bob Hepple Award for Lifetime Achievement in Labour Law 2025. - Supiot, Alain (International Labour Review, 2026)
The article focuses on the relationship between labour law and the concept of the "debt of life," as discussed in the acceptance speech for the Bob Hepple Award for Lifetime Achievement in Labour Law 2025. It critiques the neoliberal globalization model, which prioritizes market sovereignty over social justice and intergenerational solidarity, leading to ecological degradation, social inequality, and democratic decline. The author advocates reviving the project of "mondialisation" (world making), emphasizing cooperation among diverse societies, recognition of ecological and economic limits, and the intergenerational debt inherent in labour and social security law—particularly through systems like pay-as-you-go pensions that embody solidarity across generations. The article calls for labour law to promote humane working conditions, responsible use of digital technologies, and collective rights that support ecological sustainability and the well-being of future generations, aligning with the principles enshrined in the International Labour Organization’s Constitution and the Declaration of Philadelphia.